KNOWLEDGE OF DENTISTS IN MEDAN CONCERNING GREEN DENTISTRY ON RADIOLOGICAL WASTE MANAGEMENT - Manja, Cek Dara; Kartika, Dewi; Saragih, Sonia Ayunita (Universitas Baiturrahmah, 2023)
Introduction: The radiographic procedure is hazardous waste because it uses toxic materials. According to the concept of green dentistry, appropriate and efficient waste management needs to be carried out to avoid risks to human health or the environment. This study aims to determine the knowledge level of dentists in Medan concerning green dentistry in the management of radiological waste. Methods: A descriptive study was used as a study method, and purposive sampling was used to choose samples. The total sample consisted of 31 dentists in Medan who owned radiographic equipment. Data were obtained from direct questionnaires. The data were analyzed univariately and calculated in a frequency and percentage table. Result: The results showed that 100% of dentists knew about the definition of green dentistry, 83.9% about the 4R principle of green dentistry, 96.8% about the green dentistry recommendation for radiological waste management, 100% about the benefit of digital radiographic images, 93.5% about paper waste management of digital radiography, 35.5% about the silver-containing hazardous waste solution, 90.3% about how to dispose of fixer solution, 71.0% about disposing of developer solution, 93.5% about disposing of x-ray films, 71.0% about disposing of lead foil, and 45.2% about good x-ray cleaners. Conclusion: This study concludes that 87.1% of dentists in Medan had a knowledge level of green dentistry on radiological waste management in the good category, 9.7% in the fair category, and 3.2% in the less category.